Necessary energy uses and a minimum standard of living in the United Kingdom: Energy justice or escalating expectations?. (August 2016) - Walker, Gordon; Simcock, Neil; Day, Rosie
Abstract: Access to affordable energy is a core dimension of energy justice, with recent work examining the relation between energy use and well-being in these terms. However, there has been relatively little examination of exactly which energy uses should be considered basic necessities within a given cultural context and so of concern for energy justice. We examine the inclusion of energy-using necessities within the outcomes of deliberative workshops within members of the public focused on defining a minimum-standard of living in the UK and repeated biannually over a six year period. Our secondary analysis shows that energy uses deemed to be necessities are diverse and plural, enabling access to multiple valued energy services, and that their profile has to some degree shifted from 2008 to 2014. The reasoning involved is multidimensional, ranging across questions of health, social participation, opportunity and practicality. We argue that public deliberations about necessities can be taken as legitimate grounding for defining minimum standards and therefore the scope of 'doing justice' in fuel poverty policy. However we set this in tension with how change over time reveals the escalation of norms of energy dependency in a society that on climate justice grounds must radically reduce carbon emissions.